Are all GMOs the same? Consumer acceptance of cisgenic rice in India. Issue 1 (4th August 2015) - Shew, Aaron M.; Nalley, Lawton L.; Danforth, Diana M.; Dixon, Bruce L.; Nayga, Rodolfo M.; Delwaide, Anne‐Cecile; Valent, Barbara
Summary: India has more than 215 million food‐insecure people, many of whom are farmers. Genetically modified (GM) crops have the potential to alleviate this problem by increasing food supplies and strengthening farmer livelihoods. For this to occur, two factors are critical: (i) a change in the regulatory status of GM crops, and (ii) consumer acceptance of GM foods. There are generally two classifications of GM crops based on how they are bred: cisgenically bred, containing only DNA sequences from sexually compatible organisms; and transgenically bred, including DNA sequences from sexually incompatible organisms. Consumers may view cisgenic foods as more natural than those produced via transgenesis, thus influencing consumer acceptance. This premise was the catalyst for our study—would Indian consumers accept cisgenically bred rice and if so, how would they value cisgenics compared to conventionally bred rice, GM‐labelled rice and 'no fungicide' rice? In this willingness‐to‐pay study, respondents did not view cisgenic and GM rice differently. However, participants were willing‐to‐pay a premium for any aforementioned rice with a 'no fungicide' attribute, which cisgenics and GM could provide. Although not significantly different ( P = 0.16), 76% and 73% of respondents stated a willingness‐to‐consume GM and cisgenic foods, respectively.